PELATIHAN VIDEO EDITING MENGGUNAKAN APLIKASI CAPCUT UNTUK MEMBANGUN KETERAMPILAN KREATIF MASYARAKAT DI KOTA BATAM - Devega, Army Trilidia; Herasmus, Hilda; Siddiq, Raka Brama; Bahy, M. Mahdy Abiyyu (ASOSIASI IDEBAHASA KEPRI, 2025)
Video editing training is crucial for developing creative skills in the digital era, especially in the rapidly developing city of Batam. This study aims to describe the implementation and outcomes of video editing training using the CapCut application for the Batam community. CapCut was chosen for its user-friendly interface and comprehensive features on mobile devices, making it easily accessible to a wide range of audiences. The training method used was a participatory approach, where participants were actively involved in every stage, from an introduction to basic features to hands-on video editing practice. The training covered materials such as shooting techniques, merging clips, adding text, music, transition effects, and video optimization tips for various social media platforms. Evaluation was conducted through active participant observation, the results of the final video project, and a feedback survey to measure improvements in understanding and confidence. The training results showed significant improvements in participants' technical understanding and creative skills in producing engaging video content.